A Qualitative Exploration of the Perceptions of Nursing Specialists on the Integration of Nursing Technicians in Advanced Practice Roles in Hafr Elbatin - Liyanah Hazam Almutiri; Amiruh Dali Al-Dhafiri; Ghaliah Hamdan Al Rashidi; Aziza Karkan Al-Dhafiri; Mariam Manawir Aldhafiri; Hanan Alaswd Almutairi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The integration of nursing technicians into advanced practice roles has emerged as a potential solution to address the growing healthcare demands and workforce shortages in Saudi Arabia. However, little is known about the perceptions of nursing specialists regarding this integration. Objective: This qualitative study aimed to explore the perceptions of nursing specialists on the integration of nursing technicians in advanced practice roles in HafrElbatin, Saudi Arabia. Methods: Semi-structured interviews were conducted with 15 nursing specialists purposively sampled from various healthcare settings in HafrElbatin. The interviews were audio-recorded, transcribed verbatim, and analyzed using thematic analysis. Results: Four main themes emerged from the analysis: 1) Recognizing the potential of nursing technicians, 2) Concerns about patient safety and quality of care, 3) Need for clear role delineation and collaboration, and 4) Importance of education and training. Nursing specialists acknowledged the potential of nursing technicians to alleviate workforce shortages and improve access to care. However, they expressed concerns about patient safety, scope of practice, and the need for adequate education and training. Conclusions: The findings highlight the complex perceptions of nursing specialists regarding the integration of nursing technicians in advanced practice roles. While recognizing the potential benefits, addressing concerns related to patient safety, role clarity, and educational preparation is crucial for successful integration. The insights gained from this study can inform policy discussions and strategies for optimizing the nursing workforce in Saudi Arabia.